Women in medical missions on Serbian battlefields (1912-1918) - Žikić, Milena; Arsić, Jasmina; Stojkov, Svetlana; Jovanović Lješković, Nataša (Archives of Pharmacy, 2022)
During the Balkans and the First World War, the Kingdom of Serbia was faced with a shortage of medical personnel, which it compensated for with medical missions from abroad. The aim of the paper is to present the participation of women in the ranks of foreign medical missions on Serbian battlefields. Method of historical analysis by using the primary and the secondary data sources was applied. During the Balkan wars, European medical missions from Sweden, Norway, Britain, Russia, Hungary, Romania, France, the Czech Republic, Switzerland, Austria and others visited Serbia. Out of a total of 80 female students at the Swiss Medical School in Zurich, 77 were from Russia. This is a consequence of the fact that Russia had a large number of women doctors since the 19th century. European universities, such as the Zurich School of Medicine, have provided medical education to many Russian women. During the Great War, according to available data, Serbia engaged close to 2,000 medical missions from abroad, including women from Eastern and Western Europe, as well as from distant continents of America and Australia. Also, historical sources confirm the presence of pharmacists among the medical staff. The analyzed data point to the fact that a woman in the role of doctors and nurses provided medical assistance to the Serbian army in wartime circumstances, from the battlefield to the main hospital, and made a huge contribution to the war.